Barriers to access diabetic retinopathy treatment in Sri Lanka: A qualitative study - D. M. Mangala Dharmapriya Bandara Dhanapala; Mapa Prabath Piyasena; M. G. L. Mahesh Premarathna; P. F. Supun Chameera Fonseka; Sairuban K; Niruththan K; Jagjit Gilhotra; Robert Casson; Upul Senarath (AJO International)
Purpose: To explore patient and service provider perceptions on diabetic retinopathy (DR), its treatment and barriers faced by patients when accessing care, in order to develop strategies to improve uptake and outcomes of DR treatment care pathway. Study Design: A qualitative study based on 12 focus group discussions (FGDs) and 8 semi-structured interviews (SSIs) was conducted. Methods: Patients were selected from three treatment care pathways: intra-vitreal injections, laser photocoagulation and vitrectomy in a tertiary care public eye hospital. Separate FGDs were conducted for males and females, as well as Sinhalese and Tamil patients, within each treatment method to examine how gender and ethnicity influenced treatment experiences and health seeking behavior. FGDs were conducted in the two main native languages separately by two experienced sociologists. The SSIs were conducted with doctors and nurses in a language preferred by each healthcare worker. A pre-defined topic guide was used in the conduction of FGDs and SSIs. The recordings of these FGDs and SSIs were transcribed and subsequently used to conduct a thematic analysis using the Socio-Ecological Model and the health systems approach as a guide. Recurring concepts were identified by review of the transcripts which informed the development of a thematic code book. Results: A total of 73 patients participated in the FGDs with a majority being male (54.7 %, n = 40) while Sinhala was the language spoken by most (60.2 %, n = 44). A total of four doctors and four nurses were interviewed in the SSIs. The lack of knowledge on diabetes, DR and DR treatment modalities was identified as a key barrier to seeking early care and a significant contributor to patient dissatisfaction. In addition, inadequacy of infrastructure, lack of wayfinding signage systems in the hospital, behavior of healthcare assistants, discrimination, long waiting times, postponement of surgeries and inadequacy of information given by doctors were among many other sub-themes that were identified as barriers. Interviews with healthcare workers revealed lack of public awareness, overcrowding, lack of proper referral systems and inadequacy of opportunities for continuous professional development as major barriers. Conclusion: Multi-dimensional factors at all levels of the Socio-Ecological Model were found to act as barriers to patient care, principal among which was the lack of knowledge among patients on the impact of diabetes on the eye. Tailormade strategies to address these barriers should be implemented in order to improve quality of care. Patient education, staff training and infrastructure development should be the cornerstones among such measures.